More About Fundamental Laws of Lithuanian Temporary Constitution of 1919 - Maksimaitis, Mindaugas (Teisė, 2018)
The article holds an argument on the matter of constitutional development of reconstituting state of Lithuania in 1918–1920: was the second in row temporary constitutional act of 1919 the new edition of the first act of 1918, or should it be considered as a new constitution.